DOES PRE-OPENING SESSION IMPACT MARKET VOLATILITY AND LIQUIDITY? - Luluk Kholisoh; Sri Hermawati Gunadarma (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2010)
On February 4, 2004, the Indonesian Stock Exchange (IDX) was implemented the changed its trading rules from continuous open to opening call, called pre-opening session. The purpose of this trading rules changed is to improve market liquidity. Previous study found that the opening call would reduce the volatility and spread at the opening call than the continuous open. These studies analyze market volatility and liquidity (trade base and order base) using intra-day data from the Indonesian Stock Exchange, where this market uses pre-opening session as the opening call. More than 100,000 transactions were used in this study with one- month period. The results of this study are contradicts to the previous studies. Using the opening call does not reduced market volatility, especially at the opening trade. The opening trade is more volatile then closing trade. Using the opening call do not impair on liquidity, especially for high volume stocks, based on trade or based on order. This phenomenon was contradicts to the conventional wisdom which suggests that thinly traded stocks is better in call trading method while the continuous auction method is preferred for heavily traded stocks.